Effects of straw amendment on selenium aging in soils: Mechanism and influential factors - Wang, Dan; Xue, Ming-yue; Wang, Ying-kun; Zhou, De-zhi; Tang, Li; Cao, Sheng-yan; Wei, Yu-hong; Yang, Chen; Liang, Dong-Li (The Science of the total environment, 2019)
Soil dissolved organic matter (DOM) alters heavy metal availability, but whether straw amendment can manipulate soil selenium (Se) speciation and availability through DOM mineralization remains unclear. In this study, allochthonous maize straw and selenate were incubated together in four different soils for 1 y. The transformation and availability of DOM associated Se (DOM-Se) was investigated during aging. Results indicated that soil solution and soil particle surfaces were dominated by hexavalent hydrophilic acid-bound Se (Hy-Se). The amount of fulvic acid bound Se in soil solution (SOL-FA-Se) was higher than humic acid bound Se in soil solution (SOL-HA-Se), except in krasnozems, and mainly existed as hexavalent Se (Se(VI)). Tetravalent Se (Se(IV)) was the main valence state of FA-Se adsorbed on soil particle surfaces (EX-FA-Se) after 5 w of aging. The proportion of soil-available Se (SOL + EX-Se) decreased with increasing straw rate. However, under an application rate of 7500 kg·hm−2, soluble Se fraction (SOL-Se) reduction was minimal in acidic soils (18.7%–34.7%), and the organic bound Se fraction (OM-Se) was maximally promoted in alkaline soils (18.2%–39.1%). FA and HON could enhance the availability of Se in the soil solution and on particle surfaces of acidic soil with high organic matter content. While Se incorporation with HA could accelerate the fixation of Se into the solid phase of soil. Three mechanisms were involved in DOM-Se aging: (1) Reduction, ligand adsorption, and inner/outer-sphere complexation associated with the functional groups of straw-derived DOM, including hydroxyls, carboxyl, methyl, and aromatic phenolic compounds; (2) interconnection of EX-FA-Se between non-residual and residual Se pools; and (3) promotion by soil electrical conductivity (EC), clay, OM, and straw application. The dual effect of DOM on Se aging was highly reliant on the characteristics of the materials and soil properties. In conclusion, straw amendment could return selenium in soil and reduce soluble Se loss. [Display omitted] •The dynamical changes of fractionation and speciation of DOM bound Se in soils were investigated.•Straw amendment accelerated selenium retention and the reduction of hydrophilic acid bound Se.•FA and HON bound Se fraction reserved available Se while HA fraction fixed Se into soil solid phase.•EX-FA-Se indicates the soil Se availability and maintains the balance of Se within soil pools.•The acidic and phenolic functional groups were involved in DOM and Se interaction.